Implementation of moral education at Miftahul Huda Al-Ulya islamic boarding school in Sragen - Kholil Kholil; Muhammad Isa Anshory; Ngatmin Abbas; Mahdee Maduerawae (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This research aims to investigate the implementation of adab education at Pondok Pesantren Miftahul Huda Al-Ulya Donoyudan Kalijambe Sragen. The research method used is qualitative with a case study approach. The results indicate that adab education in the pesantren involves several aspects, such as respect for the asatidzah (teachers), respect for elders, mentoring and guidance for students, full participation in pondok activities, and the practice of dirasah maktabiyah. The implications of this research are that adab education in the pesantren plays a crucial role in shaping the character of students, reinforcing Islamic values, and creating a holistic educational environment.